Evaluation of the inhibition behavior of carbon dots on carbon steel in HCl and NaCl solutions. (15th April 2020) - Ye, Yuwei; Jiang, Zilong; Zou, Yangjun; Chen, Hao; Guo, Shengda; Yang, Qiumin; Chen, Liyong
Abstract: An eco-friendly and effective corrosion inhibitor (N-CDs) was acquired by hydrothermal method in methacrylic acid and ethyl(methyl)amine precursors. Afterwards, the weight loss and electrochemistry measurement were chosen to appraise the corrosion inhibition behavior of as-prepared N-CDs for Q235 steel in Cl − contained solutions. The change rules of EIS and Tafel data displayed that the as-prepared N-CDs revealed a high-efficiency protection for steel in all test environments. Meanwhile, the inhibition efficiency of steel reached up to 93.93 % (1 M HCl) and 88.96 % (3.5 wt% NaCl) at 200 mg/L of N-CDs. Furthermore, the N-CDs could form the adsorption film on steel surface to avoid the strong attack of Cl − . By analysis, the adsorption mechanism of as-prepared N-CDs on steel surface was physicochemical interaction, which strictly complied with the Langmuir adsorption model in both solutions.